2013
DOI: 10.1002/qre.1581
|View full text |Cite
|
Sign up to set email alerts
|

Outlier Detection for Healthcare Quality Monitoring – A Comparison of Four Approaches to Over‐Dispersed Proportions

Abstract: bOutlier detection among over-dispersed proportions is important in healthcare quality monitoring. We had previously introduced control limits for double-square-root chart on the basis of prediction intervals from regression-through-origin and compared our approach to common outlier detection tests. In this study, we develop our approach further by adjusting the confidence level (in the spirit of Chauvenet's criterion and Bayesian thinking) and transforming the chart into an asymmetric funnel plot. We compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“…Further work suggested that the statistical approach itself needed some care because the observed distributions of the data differs significantly from the normal distribution, which is used in funnel plots either as the assumed distribution of the data or as the approximation to the binomial distribution. More recent work (Vidmar & Blagus, 2014) demonstrated that when comparing small proportions with large denominator, such as the proportion of pupils with special educational needs in particular placements, the data tends to be overdispersed. The use of standard funnel plots may thus describe virtually all cases as outliers.…”
Section: Monitoring Policiesmentioning
confidence: 99%
“…Further work suggested that the statistical approach itself needed some care because the observed distributions of the data differs significantly from the normal distribution, which is used in funnel plots either as the assumed distribution of the data or as the approximation to the binomial distribution. More recent work (Vidmar & Blagus, 2014) demonstrated that when comparing small proportions with large denominator, such as the proportion of pupils with special educational needs in particular placements, the data tends to be overdispersed. The use of standard funnel plots may thus describe virtually all cases as outliers.…”
Section: Monitoring Policiesmentioning
confidence: 99%
“…HEXT outputs BS values for each node in each taxon-jackknife tree in a table, which can be used as input for alternative outlier tests (e.g. Vidmar & Blagus 2014).…”
Section: Evaluation Of Bootstrap Support Valuesmentioning
confidence: 99%
“…It is an important part of data mining and a very active branch of information science, which has attracted the attention of researchers in many disciplines including data mining, statistics, and information theory [2], [3]. Now, outlier detection is considered as a critical task in many practical applications, such as network intrusion detection [4]- [8], fraud detection [9]- [11], industrial damage detection [12]- [15] and health care monitoring [16]- [18].…”
Section: Introductionmentioning
confidence: 99%